Exterior of the Hazareshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The exterior of the Hazareshwar Temple is embellished with depictions of deities. The vedibandha (basal mouldings) has various ornamental elements including khura (hoof), kapotapalika (cyma recta), garggarika, karnika, grassapatta (a band of kirtimukhas or face of glory), plain patta, kumbha (pot), kalasha (pitcher), gaggarika (decorative motif comprising arrow between two spirals), and kapotapalika. On the jangha are bhadras (central offsets) on all three sides, with the space between them adorned with stambhas (buttresses) featuring motifs of peepal leaves and grassapatta. Rising above the jangha is the majestic shikhara (superstructure).